Luminescent material, anti-counterfeiting optical film and preparation method thereof
By using SrGa12-xMnxO19/Ga2O3 multimodal optical heterojunction luminescent material and PDMS polymer to prepare anti-counterfeiting optical films, the problem of single luminescent mode and poor anti-counterfeiting effect of existing inorganic phosphors is solved, and the efficient anti-counterfeiting effect of two-color luminescent and multiple excitation methods is achieved.
Patent Information
- Application Number
- CN202411918183.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing inorganic phosphors doped with lanthanides only have one luminescence mode, photoluminescence, which has poor anti-counterfeiting effect and is easy to imitate.
A multimodal optical heterojunction luminescent material of SrGa12-xMnxO19/Ga2O3 is used to achieve single-doped two-color luminescence through the regulation of heterojunction, and an anti-counterfeiting optical film is prepared in combination with PDMS polymer.
Two-color luminescence (green and red) is achieved, which enhances the luminescence intensity and afterglow duration, and has different wavelengths of light excitation, stress emission, long afterglow emission, thermal luminescence and X-ray excitation light, improving the anti-counterfeiting effect.
Smart Images

Figure CN119351084B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of luminescent materials, and in particular relates to luminescent materials, anti-counterfeiting optical films and preparation methods thereof. Background Art
[0002] Luminescent materials are becoming increasingly popular in the field of anti-counterfeiting technology due to their high sensitivity to external stimuli, easy visual observation, and compatibility with existing encryption label manufacturing processes. The excitation of luminescent materials by light of specific wavelengths and the resulting emission of different colors of light are key factors in optical anti-counterfeiting.
[0003] In order to improve the security level of anti-counterfeiting labels, traditional single-mode emission luminescent materials are now upgraded to multi-mode emission single-component luminescent materials. The developed multi-modal luminescent materials include ① coordination polymers; ② carbon dots; ③ nanocrystals; ④ lanthanide-doped inorganic phosphors. Tunable colors can be emitted by adjusting the parameters of the type of external excitation, such as ultraviolet / near-infrared light excitation, x-ray irradiation, thermal interference or mechanical stimulation.
[0004] Existing lanthanide-doped inorganic phosphors, such as rare earth ion-doped double perovskite systems, have a general chemical formula of Cs 2 NaInCl 6 :0.01Sb 3+ , 0.10Tb 3+ Through the dual doping method, electrons can be transferred to Sb 3+ of 3 P 1 Energy levels and Tb 3+ 5 D 4 Energy level, then 3 P 1 The electrons in the energy level transfer back to Sb through radiation 3+ ground state and emits 454nm blue light and 5 D 4 Energy level electron radiative transition back to Tb 3+ The ground state emits 548nm light, realizing the original Tb 3+ The ions emit light in a single green color, and then in a dual color of blue and green.
[0005] However, this doped lanthanide ion has only one luminescence mode, photoluminescence, and is usually a relatively expensive rare earth ion element, so it has a poor anti-counterfeiting effect and is easy to imitate. Summary of the invention
[0006] The purpose of the present invention is to provide a luminescent material, an anti-counterfeiting optical film and a preparation method thereof, aiming to solve the shortcomings of the prior art inorganic phosphors having only one luminescence mode, photoluminescence, poor anti-counterfeiting effect and easy imitation.
[0007] The present invention solves the above technical problems through the following technical solutions.
[0008] In one aspect, the present invention provides a luminescent material, the chemical formula of which is SrGa 12- x Mn x O 19 / Ga 2 O 3 , where x = 0.025 to 0.035, SrGa 12-x Mn x O 19 and Ga 2 O 3 The molar ratio is 1 to 19:1.
[0009] The luminescent material provided by the present invention is a multimodal optical heterojunction luminescent material. Through the regulation of the heterojunction, firstly, the internal defects of the material are reduced, the bond length of the Mn ion-Mn ion is shortened, the Mn-Mn ion pair is formed and magnetic coupling is generated, and the single-doped two-color luminescence is realized, wherein the green luminescence is due to the single Mn 2+ Ion luminescence center 4 T 1 ( 4 G) → 6 A 1 ( 6 The red luminescence is due to the Mn-Mn ion pair 4 T 1 ( 4 G) → 6 A 1 ( 6 S) transition; and the two Mn 2+ The electron spins of the ions are parallel and occupy bonding orbitals and antibonding orbitals respectively, which leads to a decrease in the energy of the electrons from the lowest excited state to the ground state. 4 T 1 ( 4 G) → 6 A 1 ( 6 S), resulting in an enhancement of red light emission; secondly, with the formation of the heterojunction, the energy band distance inside the material is shortened, which will cause the overall energy band width of the material to narrow, which reduces the energy required for electrons to transition from the ground state to the excited state, and the probability of non-radiative transitions is also reduced, resulting in a gradual increase in its luminescence intensity; the electrons stored in the trap are also more likely to transition to the rewind band and return to the excited state through the tunneling effect. 6 A 1, reducing the losses caused by non-radiative transitions, thereby enhancing the afterglow, stress and X-ray emission intensity and duration; finally, due to the formation of the heterojunction, the trap density inside the material increases, and there are three types of traps: low temperature, room temperature and high temperature. Therefore, when the luminescent material is placed on a heating table heated at 175°C, the electrons in the deep traps corresponding to the high temperature are first excited and emit red light, and as the heating table is turned off, the electrons in the shallow traps whose temperature drops to room temperature are excited again and emit green light, realizing the phenomenon of thermochromism.
[0010] The method for preparing the above-mentioned luminescent material comprises the following steps:
[0011] S1. Strontium carbonate, a first gallium oxide and a manganese carbonate compound are used as raw materials, dissolved in a solvent and ground to obtain a mixed slurry. The slurry is dried to remove the solvent to obtain a precursor.
[0012] S2. Add a second gallium oxide to the precursor, grind to obtain a mixture, calcine the mixture for the first time in an air atmosphere at a calcination temperature of 1300°C to 1400°C, and then calcine the mixture for the second time in a protective gas atmosphere containing a reducing gas at a calcination temperature of 1350°C to 1450°C. After the calcination, a luminescent material is obtained.
[0013] It should be noted that the present invention adopts the traditional high-temperature solid-phase method to prepare optical materials. Compared with other synthetic methods such as hot injection, hydrothermal method, coprecipitation, etc., this method has a simple process. Generally, it only needs to mix and grind the solid raw materials, and then calcine at high temperature for a period of time to obtain the product. The process parameters are easy to control, reproducible, and stable, because the crystal structure of the material can be made more stable during the high-temperature solid-phase reaction, thereby improving the chemical stability of the material. And the secondary sintering method is adopted, and the secondary sintering method reduces the presence of defects in the material, thereby shortening the Mn ion-Mn ion bond length, enhancing the magnetic coupling interaction, and realizing single-doped dual-color luminescence.
[0014] Furthermore, the molar ratio of the strontium carbonate, the first gallium oxide and the manganese carbonate is 1:12-x:x, where x=0.025-0.035. Preferably, x=0.03.
[0015] Furthermore, the molar ratio of the precursor to the second gallium oxide is 1 to 19: 1. Preferably, the molar ratio of the precursor to the second gallium oxide is 4:1.
[0016] It should be noted that as the doping concentration of the second gallium oxide increases, Ga 2 O 3 :Mn 2+ , and Ga 2 O 3 :Mn 2+It is completely non-luminous, so as the proportion continues to increase, the overall luminescence trend of the material shows a trend of first rising and then falling.
[0017] Furthermore, during the first calcination process, the temperature is first increased to 1000°C at a rate of 10°C / min, then increased to 1300°C-1400°C at a rate of 5°C / min, and calcined at 1300°C-1400°C for 5.5h-6.5h.
[0018] Furthermore, during the second calcination, the temperature is first raised to 1000°C at a rate of 10°C / min, then raised to 1350°C-1450°C at a rate of 5°C / min, and calcined at 1350°C-1450°C for 5.5h-6.5h, and the protective gas containing the reducing gas is N 2 / H 2 Mixed gas, N 2 and H 2 The volume ratio is 16-18:1.
[0019] The present invention also provides the application of the above-mentioned luminescent material in anti-counterfeiting materials. The luminescent material has light-stimulated luminescence, long afterglow luminescence, thermoluminescence and X-ray-stimulated luminescence of different wavelengths. It can emit 502nm green light under 254nm light excitation and 655nm red light under 380nm light excitation; after 254nm light excitation for 5min, the luminescent material can emit 15min of green afterglow luminescence, and can emit 30min of red afterglow luminescence after 380nm light excitation for 5min. The initial intensity is very high, but the intensity decays relatively quickly; the luminescent material can continuously emit 15min of afterglow luminescence after X-ray excitation for 5min; the luminescent material can produce obvious thermochromic luminescence under a heating table above 125°C. The luminescent material first emits obvious red light, and as the heating table is turned off and the temperature drops, the luminescent material will emit green light again and gradually dim, realizing the phenomenon of thermochromism, which solves the disadvantages of the prior art that inorganic phosphors have only one luminescence mode, photoluminescence, poor anti-counterfeiting effect and are easy to imitate.
[0020] On the other hand, the present invention provides an anti-counterfeiting optical film prepared using the above-mentioned luminescent material.
[0021] The method for preparing the anti-counterfeiting optical film comprises the following steps:
[0022] The luminescent material, PDMS polymer and curing agent are uniformly mixed to obtain a colloid, and an anti-counterfeiting optical film is obtained after curing. The mass ratio of the luminescent material to the PDMS polymer is 1:0.65-1.5, and the mass ratio of the PDMS polymer to the curing agent is 9-10:1.
[0023] It should be noted that PDMS is polydimethylsiloxane. Since PDMS is an acceptor material, it is easier to attract electric charges than other polymers. When PDMS is under pressure, it can sense and generate piezoelectric potential. The stress luminescence of the luminescent material-PDMS composite material is an electroluminescent phenomenon caused by the internal friction electricity generated at the interface between the particles in the phosphor and the elastic polymer matrix. When the film is subjected to stress, an induced electromotive force is generated, which stimulates the electrons in the traps inside the material to overflow, thereby generating luminescence.
[0024] The present invention also provides the application of the above-mentioned anti-counterfeiting optical film in anti-counterfeiting materials. The anti-counterfeiting optical film prepared by mixing the luminescent material and PDMS can emit obvious green light under tension or pressure. The tested film can restore stress luminescence when irradiated with 265nm or 380nm light, and the stress luminescence intensity is stronger than the afterglow luminescence intensity.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The luminescent material provided by the present invention is a multimodal optical heterojunction luminescent material. Through the regulation of the heterojunction, firstly, the internal defects of the material are reduced, the bond length of the Mn ion-Mn ion is shortened, the Mn-Mn ion pair is formed and magnetic coupling is generated, and the single-doped two-color luminescence is realized, wherein the green luminescence is due to the single Mn 2+ Ion luminescence center 4 T 1 ( 4 G) → 6 A 1 ( 6 The red luminescence is due to the Mn-Mn ion pair 4 T 1 ( 4 G) → 6 A 1 ( 6 S) transition; and the two Mn 2+ The electron spins of the ions are parallel and occupy bonding orbitals and antibonding orbitals respectively, which leads to a decrease in the energy of the electrons from the lowest excited state to the ground state. 4 T 1 ( 4 G) → 6 A 1 ( 6 S), resulting in an enhancement of red light emission; secondly, with the formation of the heterojunction, the energy band distance inside the material is shortened, which will cause the overall energy band width of the material to narrow, which reduces the energy required for electrons to transition from the ground state to the excited state, and the probability of non-radiative transitions is also reduced, resulting in a gradual increase in its luminescence intensity; the electrons stored in the trap are also more likely to transition to the rewind band and return to the excited state through the tunneling effect.6 A 1 , reducing the losses caused by non-radiative transitions, thereby enhancing the afterglow, stress and X-ray emission intensity and duration; finally, due to the formation of the heterojunction, the trap density inside the material increases, and there are three types of traps: low temperature, room temperature and high temperature. Therefore, when the material is placed on a heating table heated at 175°C, the electrons in the deep traps corresponding to the high temperature are first excited and emit red light, and as the heating table is turned off, the electrons in the shallow traps whose temperature drops to room temperature are excited again and emit green light, realizing the phenomenon of thermochromism.
[0027] 2. The luminescent material and anti-counterfeiting optical film provided by the present invention have five types of light, namely, light-induced luminescence, stress luminescence, long afterglow luminescence, thermoluminescence and X-ray luminescence with different wavelengths. The luminescent material can emit 502nm green light under 254nm light excitation and 655nm red light under 380nm light excitation. After 254nm light excitation for 5min, the luminescent material can emit green afterglow luminescence for 15min, and can emit red afterglow luminescence for 30min after 380nm light excitation for 5min. The initial intensity is very high, but the intensity decays relatively quickly. The luminescent material can emit a continuous afterglow for 15 minutes when excited by X-rays for 5 minutes. The luminescent material can produce obvious thermochromic luminescence under a heating platform above 125°C. The luminescent material first emits obvious red light, and as the heating platform is turned off and the temperature drops, the luminescent material will emit green light and gradually dim. The anti-counterfeiting optical film prepared by mixing the luminescent material with PDMS can emit obvious green light under tension or pressure. The tested anti-counterfeiting optical film can recover stress luminescence when irradiated with 265nm or 380nm light, and the stress luminescence intensity is stronger than the afterglow luminescence intensity. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a photoluminescence performance diagram of the luminescent materials of Examples 1 to 5 of the present invention and Comparative Example 1.
[0029] Figure 2 The luminescent materials of Examples 1 to 5 of the present invention and Comparative Example 1 are luminescent images at different excitation wavelengths.
[0030] Figure 3 Afterglow performance diagram of the luminescent materials of Examples 1 to 5 of the present invention and Comparative Example 1.
[0031] Figure 4 This is a physical picture of the afterglow performance of the luminescent material in Example 2 of the present invention.
[0032] Figure 5 The thermoluminescence spectra of the luminescent materials of Examples 1 to 5 and Comparative Example 1 of the present invention are shown.
[0033] Figure 6 This is a flow chart of the thermochromic change of the luminescent material prepared in Example 2 of the present invention after heating and turning off the heating.
[0034] Figure 7 This is a stress test diagram of the anti-counterfeiting optical film prepared in Examples 6 to 9 of the present invention.
[0035] Figure 8 Actual pictures of stress luminescence of anti-counterfeiting optical films prepared in Examples 6 to 9 of the present invention.
[0036] Fig. 9 This is a graph of afterglow attenuation curves of the anti-counterfeiting optical films prepared in Examples 6 to 9 of the present invention under X-ray excitation. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Certain words are used in the present invention to refer to specific components. It should be understood by those skilled in the art that technicians will use different nouns to refer to the same component. The present invention does not distinguish the components by the difference in nouns, but by the difference in functions of the components.
[0039] The invention is further described below through specific examples.
[0040] Example 1
[0041] A method for preparing a luminescent material, synthesized by a high-temperature solid phase method, comprises the following steps:
[0042] S1, according to the chemical formula of the luminescent material is SrGa 12-0.03 Mn 0.03 O 19 / Ga 2 O 3 According to the stoichiometric ratio in the raw materials, strontium carbonate, gallium oxide and manganese carbonate compound are weighed, and strontium carbonate, gallium oxide and manganese carbonate compound are added into 5 ml of anhydrous ethanol solvent for grinding to obtain a mixed slurry. After drying the slurry to remove the solvent, a precursor is obtained.
[0043] S2. The precursor and gallium oxide were placed in an agate mortar at a molar ratio of 0.9:0.1, 5 ml of anhydrous ethanol was added and ground for 15 minutes, and the ground powder was placed in a 90°C drying oven to remove water for 15 minutes. The dried powder was taken out and placed in a crucible, and heated to 1000°C at a rate of 10°C / min in an air atmosphere, and then heated to 1350°C at a rate of 5°C / min, and calcined at 1350°C for 6 hours; then heated to 1000°C at a rate of 10°C / min in a protective gas atmosphere containing a reducing gas, and then heated to 1400°C at a rate of 5°C / min, and calcined at 1400°C for 6 hours. The protective gas containing a reducing gas is N 2 / H 2 Mixed gas, N 2 and H 2 The volume ratio of Mn / GO is 95:5. After calcination, the luminescent material is obtained by natural cooling and named SGO / GO:Mn 2+ .
[0044] Example 2
[0045] A method for preparing a luminescent material, synthesized by a high-temperature solid phase method, comprises the following steps:
[0046] S1, according to the chemical formula of the luminescent material is SrGa 12-0.03 Mn 0.03 O 19 / Ga 2 O 3 According to the stoichiometric ratio in the raw materials, strontium carbonate, gallium oxide and manganese carbonate compound are weighed, and strontium carbonate, gallium oxide and manganese carbonate compound are added into 5 ml of anhydrous ethanol solvent for grinding to obtain a mixed slurry. After drying the slurry to remove the solvent, a precursor is obtained.
[0047] S2. The precursor and gallium oxide were placed in an agate mortar at a molar ratio of 0.8:0.2, 5 ml of anhydrous ethanol was added and ground for 15 minutes, and the ground powder was placed in a 90°C drying oven to remove water for 15 minutes. The dried powder was taken out and placed in a crucible, and heated to 1000°C at a rate of 10°C / min in an air atmosphere, and then heated to 1350°C at a rate of 5°C / min, and calcined at 1350°C for 6 hours; then heated to 1000°C at a rate of 10°C / min in a protective gas atmosphere containing a reducing gas, and then heated to 1400°C at a rate of 5°C / min, and calcined at 1400°C for 6 hours. The protective gas containing a reducing gas is N 2 / H 2 Mixed gas, N 2 and H 2The volume ratio of Mn / GO is 95:5. After calcination, the luminescent material is obtained by natural cooling and named SGO / GO:Mn 2+ .
[0048] Example 3
[0049] A method for preparing a luminescent material, synthesized by a high-temperature solid phase method, comprises the following steps:
[0050] S1, according to the chemical formula of the luminescent material is SrGa 12-0.03 Mn 0.03 O 19 / Ga 2 O 3 According to the stoichiometric ratio in the raw materials, strontium carbonate, gallium oxide and manganese carbonate compound are weighed, and strontium carbonate, gallium oxide and manganese carbonate compound are added into 5 ml of anhydrous ethanol solvent for grinding to obtain a mixed slurry. After drying the slurry to remove the solvent, a precursor is obtained.
[0051] S2. The precursor and gallium oxide were placed in an agate mortar at a molar ratio of 0.7:0.3, 5 ml of anhydrous ethanol was added and ground for 15 minutes, and the ground powder was placed in a 90°C drying oven to remove water for 15 minutes. The dried powder was taken out and placed in a crucible, and heated to 1000°C at a rate of 10°C / min in an air atmosphere, and then heated to 1350°C at a rate of 5°C / min, and calcined at 1350°C for 6 hours; then heated to 1000°C at a rate of 10°C / min in a protective gas atmosphere containing a reducing gas, and then heated to 1400°C at a rate of 5°C / min, and calcined at 1400°C for 6 hours. The protective gas containing a reducing gas is N 2 / H 2 Mixed gas, N 2 and H 2 The volume ratio of Mn / GO is 95:5. After calcination, the luminescent material is obtained by natural cooling and named SGO / GO:Mn 2+ .
[0052] Example 4
[0053] A method for preparing a luminescent material, synthesized by a high-temperature solid phase method, comprises the following steps:
[0054] S1, according to the chemical formula of the luminescent material is SrGa 12-0.03 Mn 0.03 O 19 / Ga 2 O 3Strontium carbonate, gallium oxide and manganese carbonate were weighed according to the stoichiometric ratio in the reaction mixture. Strontium carbonate, gallium oxide and manganese carbonate were added into 5 ml of anhydrous ethanol solvent for grinding to obtain a mixed slurry. The slurry was dried to remove the solvent to obtain a precursor named SGO / GO:Mn 2+ .
[0055] S2. The precursor and gallium oxide were placed in an agate mortar at a molar ratio of 0.5:0.5, 5 ml of anhydrous ethanol was added and ground for 15 minutes, and the ground powder was placed in a 90°C drying oven to remove water for 15 minutes. The dried powder was taken out and placed in a crucible, and heated to 1000°C at a rate of 10°C / min in an air atmosphere, and then heated to 1350°C at a rate of 5°C / min, and calcined at 1350°C for 6 hours; then heated to 1000°C at a rate of 10°C / min in a protective gas atmosphere containing a reducing gas, and then heated to 1400°C at a rate of 5°C / min, and calcined at 1400°C for 6 hours. The protective gas containing a reducing gas is N 2 / H 2 Mixed gas, N 2 and H 2 The volume ratio of Mn / GO is 95:5. After calcination, the luminescent material is obtained by natural cooling and named SGO / GO:Mn 2+ .
[0056] Example 5
[0057] A method for preparing a luminescent material, synthesized by a high-temperature solid phase method, comprises the following steps:
[0058] S1, according to the chemical formula of the luminescent material is SrGa 12-0.03 Mn 0.03 O 19 / Ga 2 O 3 According to the stoichiometric ratio in the raw materials, strontium carbonate, gallium oxide and manganese carbonate compound are weighed, and strontium carbonate, gallium oxide and manganese carbonate compound are added into 5 ml of anhydrous ethanol solvent for grinding to obtain a mixed slurry. After drying the slurry to remove the solvent, a precursor is obtained.
[0059] S2. The precursor and gallium oxide were placed in an agate mortar at a molar ratio of 0.95:0.05, 5 ml of anhydrous ethanol was added and ground for 15 minutes, and the ground powder was placed in a 90°C drying oven to remove water for 15 minutes. The dried powder was taken out and placed in a crucible, and heated to 1000°C at a rate of 10°C / min in an air atmosphere, and then heated to 1350°C at a rate of 5°C / min, and calcined at 1350°C for 6 hours; then heated to 1000°C at a rate of 10°C / min in a protective gas atmosphere containing a reducing gas, and then heated to 1400°C at a rate of 5°C / min, and calcined at 1400°C for 6 hours. The protective gas containing a reducing gas is N 2 / H 2 Mixed gas, N 2 and H 2 The volume ratio of Mn / GO is 95:5. After calcination, the luminescent material is obtained by natural cooling and named SGO / GO:Mn 2+ .
[0060] Comparative Example 1
[0061] A method for preparing a luminescent material, synthesized by a high-temperature solid phase method, comprises the following steps:
[0062] S1, according to the chemical formula of the luminescent material is SrGa 12-0.03 Mn 0.03 O 19 According to the stoichiometric ratio in the raw materials, strontium carbonate, gallium oxide and manganese carbonate compound are weighed, and strontium carbonate, gallium oxide and manganese carbonate compound are added into 5 ml of anhydrous ethanol solvent for grinding to obtain a mixed slurry. After drying the slurry to remove the solvent, a precursor is obtained.
[0063] S2. Put the precursor into an agate mortar, add 5 ml of anhydrous ethanol and grind for 15 minutes, and put the ground powder into a 90°C drying oven to remove water for 15 minutes. Take out the dried powder and put it into a crucible. In an air atmosphere, heat it to 1000°C at a rate of 10°C / min, then heat it to 1350°C at a rate of 5°C / min, and calcine it at 1350°C for 6 hours; then heat it to 1000°C at a rate of 10°C / min in a protective gas atmosphere containing a reducing gas, then heat it to 1400°C at a rate of 5°C / min, and calcine it at 1400°C for 6 hours. The protective gas containing a reducing gas is N 2 / H 2 Mixed gas, N 2 and H 2 The volume ratio is 95:5. After calcination, the luminescent material is obtained by natural cooling.
[0064] The luminescent materials prepared in Examples 1 to 5 and the luminescent material prepared in Comparative Example 1 were tested for structure and performance, and the results are as follows:
[0065] Figure 1 The photoluminescence performance diagram of the luminescent materials of Examples 1 to 5 of the present invention and Comparative Example 1 is shown. Figure 1 As shown in the figure, under the excitation of 380nm light, the emission spectrum shows double peaks of 502nm and 655nm corresponding to green light and red light respectively. As the proportion of heterojunction increases, the internal defects of the material decrease, the bond length of Mn ion-Mn ion shortens, Mn-Mn ion pairs are formed and magnetic coupling is generated, resulting in a decrease in the energy of electrons transitioning from the lowest excited state back to the ground state, that is, 4 T 1 ( 4 G) → 6 A 1 ( 6 S), which produces red luminescence. It is generally believed that green luminescence is due to the single Mn 2+ Ion luminescence center 4 T 1 ( 4 G) → 6 A 1 ( 6 The red luminescence is due to the Mn-Mn ion pair 4 T 1 ( 4 G) → 6 A 1 ( 6 S) transition. And with the formation of heterojunction, the energy band distance inside the material is shortened, which reduces the energy required for electrons to transition from the ground state to the excited state, and the probability of non-radiative transition is also reduced, resulting in a gradual increase in its luminescence intensity. The luminescence intensity is strongest when the heterojunction ratio is 0.8 / 0.2, and then as the gallium oxide concentration increases, concentration quenching occurs and the intensity decreases.
[0066] Actual fluorescence images of the luminescent materials of Examples 1 to 5 and Comparative Example 1 were captured by a professional camera. Since currently commercial UV flashlights only have 365nm and no precise counterpart to 380nm, 365nm was used to replace 380nm light for excitation for illustration. Figure 2 The luminescent materials of Examples 1 to 5 and Comparative Example 1 of the present invention are luminescent materials at different excitation wavelengths. At this time, the luminescent materials of Examples 1 to 5 and Comparative Example 1 are named SGO / GO. Figure 2As shown, it can emit green light under 254nm light excitation and red light under 365nm light excitation. The luminescence intensity is strongest when the heterojunction ratio is 0.8 / 0.2. Then, as the gallium oxide concentration increases, concentration quenching occurs and the intensity decreases.
[0067] Figure 3 Afterglow performance diagram of the luminescent materials of Examples 1 to 5 of the present invention and Comparative Example 1. Figure 3 As shown, after 5 minutes of light excitation at 380 nm, the afterglow spectrum shows afterglow luminescence lasting up to half an hour, among which the initial intensity and duration of the afterglow are the longest when the heterojunction ratio is 0.8 / 0.2.
[0068] Figure 4 This is a physical picture of the afterglow performance of the luminescent material of Example 2 of the present invention. Figure 4 As described above, after 5 minutes of excitation with 254nm light, the green light gradually disappeared after 15 minutes, while after 5 minutes of excitation with 365nm light, the green light gradually disappeared after 25 minutes, showing a luminescence that lasted up to half an hour.
[0069] The thermoluminescence spectrum of the phosphor is tested. Thermoluminescence can measure the trap properties inside a material. The trap can temporarily capture excited electrons in the material and release the electrons after the excitation ends. Figure 5 The thermoluminescence spectra of the luminescent materials of Examples 1 to 5 and Comparative Example 1 of the present invention are shown in FIG. Figure 5 As shown in the figure, as the heterojunction ratio increases, the three traps all move towards the low temperature direction, which explains why the afterglow time becomes longer. The thermoluminescence intensity is the strongest when the heterojunction ratio is 0.8 / 0.2, indicating that the trap density is the highest at this time, which also explains why the afterglow intensity and stress intensity are the highest under this heterojunction ratio.
[0070] The luminescent material prepared in Example 2 was subjected to a thermoluminescence test. The thermoluminescence was obtained by photographing the phosphor on a JFTOOLS heating stage with a professional camera. Figure 6 This is a flow chart of the thermochromic change of the luminescent material prepared in Example 2 of the present invention after heating and turning off the heating. Figure 6 As shown, under a heating stage above 125°C, the phosphor can produce obvious thermochromic luminescence. The phosphor first emits obvious red light, and as the heating stage is turned off and the temperature drops, the phosphor will emit green light and gradually dim.
[0071] Example 6
[0072] An anti-counterfeiting optical film is prepared using the luminescent material prepared in Example 1, comprising the following steps:
[0073] The luminescent material of Example 1 was mixed with the PDMS polymer in a mass ratio of 1:1, and then a curing agent was added, the mass ratio of the PDMS polymer to the curing agent was 10:1, and the mixture was evenly mixed to obtain a colloid, which was placed in a drying oven at 70°C for curing for 2 hours to obtain an anti-counterfeiting optical film.
[0074] Example 7
[0075] An anti-counterfeiting optical film is prepared using the luminescent material prepared in Example 2, comprising the following steps:
[0076] The luminescent material of Example 2 was mixed with the PDMS polymer at a mass ratio of 1:1, and then a curing agent was added, the mass ratio of the PDMS polymer to the curing agent was 10:1, and the mixture was evenly mixed to obtain a colloid, which was placed in a drying oven at 70°C for curing for 2 hours to obtain an anti-counterfeiting optical film.
[0077] Example 8
[0078] An anti-counterfeiting optical film is prepared using the luminescent material prepared in Example 3, comprising the following steps:
[0079] The luminescent materials of Example 3 were mixed with PDMS polymer at a mass ratio of 1:1, and then a curing agent was added, the mass ratio of PDMS polymer to curing agent was 10:1, and mixed evenly to obtain a colloid, which was placed in a drying oven at 70°C for curing for 2 hours to obtain an anti-counterfeiting optical film.
[0080] Example 9
[0081] An anti-counterfeiting optical film is prepared using the luminescent material prepared in Example 4, comprising the following steps:
[0082] The luminescent materials of Example 4 were mixed with PDMS polymer in a mass ratio of 1:1, and then a curing agent was added, the mass ratio of PDMS polymer to curing agent was 10:1, and mixed evenly to obtain a colloid, which was placed in a drying oven at 70°C for curing for 2 hours to obtain an anti-counterfeiting optical film.
[0083] The structures and properties of the anti-counterfeiting optical films prepared in Examples 6 to 9 above were tested, and the results are as follows:
[0084] Figure 7 This is a stress test diagram of the anti-counterfeiting optical film prepared in Examples 6 to 9 of the present invention. Figure 7 As shown, the prepared anti-counterfeiting optical film was subjected to a stress test. Under the condition of ensuring that the stretching amount was 12 mm, the stress spectrum showed an obvious green luminescence at 502 nm, and the stress intensity reached the highest when the heterojunction ratio was 0.8 / 0.2.
[0085] Figure 8The stress luminescence images of the anti-counterfeiting optical films prepared in Examples 6 to 9 of the present invention are shown in FIG. Figure 8 As described above, when the anti-counterfeiting optical film is subjected to stress stretching, the anti-counterfeiting optical films prepared in Examples 6 to 9 emit green light under the action of stress, and the stress intensity reaches the highest when the heterojunction ratio is 0.8 / 0.2.
[0086] Since the instrument cannot measure the spectrum for X-ray excitation, it can only obtain the afterglow spectrum. Fig. 9 The afterglow attenuation curves of the anti-counterfeiting optical films prepared in Examples 6 to 9 of the present invention under X-ray excitation are shown in FIG. Fig. 9 As shown, after 10 minutes of X-ray excitation, the afterglow spectrum shows an afterglow luminescence lasting up to 15 minutes, among which the initial intensity and duration of the afterglow are the longest when the heterojunction ratio is 0.8 / 0.2.
[0087] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0088] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A luminescent material, characterized in that: The chemical formula of the luminescent material is SrGa 12-x Mn x O 19 / Ga2O3, where x = 0.025 to 0.035, SrGa 12-x Mn x O 19 The molar ratio of Ga2O3 is 1 to 19:
1.
2. A method for preparing the luminescent material according to claim 1, characterized in that: The high temperature solid phase method is used for synthesis, including the following steps: Strontium carbonate, first gallium oxide and manganese carbonate compound are used as raw materials, dissolved in a solvent and ground to obtain a mixed slurry, and the slurry is dried to remove the solvent to obtain a precursor; A second gallium oxide is added to the precursor, and a mixture is obtained after grinding. The mixture is calcined for the first time in an air atmosphere at a calcination temperature of 1300°C to 1400°C, and then calcined for the second time in a protective gas atmosphere containing a reducing gas at a calcination temperature of 1350°C to 1450°C. After the calcination, a luminescent material is obtained.
3. The method for preparing the luminescent material according to claim 2, characterized in that: The molar ratio of the strontium carbonate, the first gallium oxide and the manganese carbonate is 1:12-x:x, where x=0.025-0.
035.
4. The method for preparing a luminescent material according to claim 2, characterized in that: The molar ratio of the precursor to the second gallium oxide is 1-19:
1.
5. The method for preparing a luminescent material according to claim 2, characterized in that: During the first calcination process, the temperature is first increased to 1000°C at a rate of 10°C / min, then increased to 1300°C-1400°C at a rate of 5°C / min, and calcined at 1300°C-1400°C for 5.5h-6.5h.
6. The method for preparing a luminescent material according to claim 2, characterized in that: During the second calcination process, the temperature is first raised to 1000°C at a rate of 10°C / min, then raised to 1350°C~1450°C at a rate of 5°C / min, and calcined at 1350°C~1450°C for 5.5h~6.5h. The protective gas containing reducing gas is N2 / H2 mixed gas, and the volume ratio of N2 to H2 is 16~18:
1.
7. An anti-counterfeiting optical film, characterized in that: The luminescent material is prepared using the luminescent material described in claim 1.
8. A method for preparing the anti-counterfeiting optical film according to claim 7, characterized in that: The following steps are involved: The luminescent material, PDMS polymer and curing agent are uniformly mixed to obtain a colloid, and after curing, a light-proof anti-counterfeiting optical film is obtained.
9. The method for preparing the anti-counterfeiting optical film according to claim 8, characterized in that: The mass ratio of the luminescent material to the PDMS polymer is 1:0.65-1.5, and the mass ratio of the PDMS polymer to the curing agent is 9-10:1.
Citation Information
Patent Citations
Blue or green fluorescent material for field emission
CN101864310A
Mechanoluminescence fluorescent powder with adjustable luminescence color and intensity, and preparation method and application thereof
CN118895122A